Penguatan Kompetensi Literasi dan Numerasi Guru Sekolah Dasar di Kabupaten Pandeglang dan Kota Serang Banten - Encep Andriana; Rina Yuliana; Indhira Asih Vivi Yandari (FKIP Universitas Sebelas Maret, 2024)
This paper aims to describe the implementation of strengthening literacy andnumeracy competencies in the city of Serang and Pandeglang district. Thesubjects of dedication, namely SDN Banjarwangi and SDN Purut were chosenas partners because they have the potential for the majority of teachers tohave high motivation and awareness to develop their potential andprofessionalism. The method of implementing community service is carriedout through four stages, including 1) Preparation, which is carried out toprepare for the implementation of community service. 2) Implementation, thisstage is carried out through training/workshop activities for teachers inselected elementary schools. 3) Assistance, this stage is carried out by forminga group team and assisting the service participants. and 4) Reporting, this stageis carried out by the team by compiling a report on the implementation of theservice. The results of this community service activity includetraining/workshop activities and mentoring that can provide knowledge andexperience in improving literacy and numeracy professional competence aswell as skills in developing literacy and numeracy-based learning tools suitablefor learning for elementary school students.